PENGARUH KOMPETENSI DAN OBJEKTIVITAS TERHADAP KUALITAS ADIT DENGAN ETIKA PROFESI SEBAGAI VARIABEL PEMODERASI DI BPK RI PERWAKILAN PROVINSI BALI - I Made Suryana Wibawa; Sang Ayu Putu Arie Indraswarawati; I Putu Nuratama (UNHI Press, 2021)
The quality of the examination results is a report on the results of the examination that contains the existence weaknesses in internal control, fraud, deviations from regulatory requirements legislation, and non-compliance must be accompanied by a response from the leadership or the official responsible for the entity being examined regarding findings and recommendations and planned corrective actions. This research aims to examine the effect of competence and objectivity on audit quality with professional ethics as a moderating variable. Where the sampling technique uses techniques purposive sampling with the criteria of auditors who have worked for 1 year as well have a minimum education level of bachelor (S1). The results of the study showed that audit competence and audit objectivity affect audit quality. And professional ethics can moderate competence and objectivity to audit quality. So two hypotheses are accepted and two hypotheses are not accepted.